Evidence of a Hypercoagulable State in Patients with Acute Lymphoblastic Leukemia Treated with Low Dose of E.coli L-Asparaginase: A GIMEMA Study - Leone, Giuseppe; Gugliotta, Luigi; Mazzucconi, Maria Gabriella; De Stefano, Valerio; Belmonte, Monica Mattioli; Dragoni, Francesco; Specchia, Giorgina; Centra, Antonietta; Gamba, Gabriella; Camera, Andrea; Mandelli, Franco (Thrombosis and Haemostasis, 1993)
Blood coagulation abnormalities induced by administration of E. coli L-asparaginase were investigated in 25 patients with acute lymphoblastic leukemia treated according to the GIMEMA ALL 0288 trial. Dosage of L-asparaginase was relatively low (6,000 U/m2/day for 7 days total dose 42,000 U/m2) as compared to the conventional dosages (120,000-140,000 U/m2 over 10–14 days). A significant decrease in fibronogen, plasminogen, alpha2-antiplasmin and antithrombin III was observed from day IV of L-asparaginase and it was maximum on day VIII, with return to the baseline levels on day XV. Protein C levels had only a borderline reduction, while no modification of protein S or factor VII was observed. Two of the patients investigated developed thrombosis. The presence of a prothrombotic state induced even by this low dosage of E. coli L-asparaginase was suggested by a significant increase of sensitive markers of hypercoagulability such as fibrinopeptide A, thrombin-antithrombin complexes, and prothrombin fragment F1 + 2.